KARAKTERISTIK PAPAN PARTIKEL BERBAHAN SEKAM PADI DENGAN PENAMBAHAN PARAFIN - Folmer Pardosi; Tamrin Latief; Filli Pratama (Jurnal Teknik Pertanian Sriwijaya, 2012)
The objective of this research was to analyze the physical and mechanical characteristics of particle board of different size of rice husks particle with the addition of paraffin.  The research used Factorial Completely Randomized Design that consisted of two treatment as factors, and each factor consisted of three levels.  Each combination of treatment was replicated three times.  The first factor was the size of rice husks particle (1.70 mm, 1.40 mm, 1.18 mm) and the second factor was the addition of paraffin (0%, 2%, 4%) based on dry weight of rice husks.  The parameters were the density, moisture content, thickness swelling, modulus of elasticity, modulus of rupture, and internal bond.  The results showed that the treatment combination between the particle size of 1.18 mm and the paraffin addition of 4% (A3B3) was the best treatment with the density of 438 kg/m3, moisture content of 9,04%, thickness swelling of 0,86%, modulus of elasticity of 28,33 N/mm2, modulus of rupture of 0,22 N/mm2, and internal bond of 0,12 N/mm2.  Keywords : Particle board, rice husk, paraffin